Evaluation of axillary lymph node status after axillary dissection in patients with SLN negative or single SLN positive T1 and T2 breast cancer (Annals of Medical Research, 2021)
Aim: The most substantial factor determining prognosis in breast cancer is axillary lymph node involvement. Therefore, axillary lymph node status should be evaluated correctly in the staging of the disease and determining the prognosis. In this study, we aim to evaluate the detection rate of metastatic lymph nodes after axillary dissection in patients with negative or single positive sentinel lymph nodes in early-stage breast cancer.Materials and Methods: We have included patients with sentinel lymph node biopsy and/or axillary dissection diagnosed with early-stage (T1 and T2) breast cancer between 2018 and 2019 in the study. We have evaluated tumor prognostic factors from patient files and the total number of lymph nodes and tumor positive lymph nodes from pathology paraffin specimens.Results: The study included 29 female patients with an average age of 56 (34-83). Breast-conserving surgery (BCS)+SLNB was performed in 15 patients and BCS+ AD in 11 patients and modified radical mastectomy (MRM) was performed in 3 patients. In 3 patients with positive surgical margin after BCS + SLN, although one patient was positive and the other two patients were negative in SLN, multiple metasatic lymph nodes were detected after axillary dissection due to the patients' request for axillary dissection. Patients were followed-up for an average of 26 months without recurrence or metastasis. Conclusion: Considering that there may be lymph node metastasis other than the sentinel lymph node in patients with SLNB negatives or single positive sentinel lymph node, we recommend more than one lymph node excision in addition to the stained lymph node.
Keywords: Axillary dissection; early stage breast cancer; sentinel lymph node; sentinel lymph node biopsy